The impact of COVID-19 on mental health: Public perceptions of community pharmacist’s role in mental health support - Alshayban, Dhafer; Althani, Rawad; Alhawashim, Safa; Joseph, Royes; Chandralla, Veerendra; Al Jamea, Zainab; Alsulaiman, Layan; Islam, Md. Ashraful; Alshehail, Bashayer; Alotaibi, Fawaz M.; Kurdi, Sawsan M.; Asiri, Ibrahim M.; et al. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The global impact of COVID-19 on mental health has been enormous. Community pharmacists are frontline healthcare providers and serve as direct access points for patients. This research sought to assess how the public in Saudi Arabia perceived and accepted the role of community pharmacists in providing mental health support during the COVID-19 pandemic. Methods: An online cross-sectional study was conducted among the Saudi public aged 18 years or above using the QuestionPro platform. The validated bilingual (English and Arabic) questionnaire was simple and detailed. One key item assessed participants’ agreement with the statement, “Pharmacists can counsel people on psychological issues,” using a five-point Likert scale. The survey link was distributed via social media platforms. Results: A total of 773 participants completed the survey. Majority were female (65.2%), age between 18 to 24 years (48.1%). Nearly half of the participants disagreed with the statement that pharmacists could provide support on psychological issues, while 19% agreed. Age, employment status, and the way psychological issues were managed during the pandemic showed a significant association with the public’s acceptance of community pharmacists’ role in delivering mental health services (p<0.001). Conclusions: Despite accessibility to community pharmacists during the pandemic, participants showed a clear preference to consult physicians regarding mental health issues. This suggests lack of acceptance to community pharmacist’s role in providing mental health support. Future research should explore barriers to public acceptance of community pharmacists in mental health support. Furthermore, policymakers are encouraged to develop and implement initiatives aimed at enhancing public awareness of the pharmacists’ contribution to mental health promotion.